REGULASI PERSAINGAN USAHA DALAM MENCEGAH PRAKTIK TIDAK SEHAT PADA SECURITIES CROWDFUNDING - Astuti, Nanin Koeswidi; Dewantara, Reka (Fakultas Hukum Universitas Kristen Indonesia, 2024)
This article examines the role of Business Competition Regulation in curbing unhealthy practices within Securities Crowdfunding (SCF). It seeks to assess the efficacy of current legal regulations regarding business competition in preventing such malpractices in SCF. The regulations set forth by the Indonesia Financial Services Authority (Peraturan Otoritas Jasa Keuangan - POJK), which oversee SCF, necessitate an effective harmonization with Business Competition Law or anti-monopoly legislation to ensure the integrity and efficiency of the financial market. The synergy between SCF regulations and Law No. 5/1999, concerning the Prohibition of Monopoly Practices and Unhealthy Business Competition, is crucial for establishing a fair and transparent capital market. The consistent application and enforcement of this law are anticipated to reinforce Indonesia's economic foundation, facilitate more efficient economic growth, and foster a reliable investment climate for business entities. Therefore, the advancement of SCF in contributing to economic progress hinges on meticulous regulatory harmonization and stringent law enforcement, thus positioning Indonesia as a key player in the dynamic global economy.